Sistem Absensi Desktop Menggunakan Face Recognition dan Pendekatan Adaptive Attendance Monitoring - Afandy, Imam; Akbar, Fawwaz Ali; Mumpuni, Retno (Komunitas Dosen Indonesia, 2026)
Manual attendance processes in higher education often face severe constraints regarding time inefficiency and vulnerability to data manipulation, specifically the prevalent issue of proxy attendance. Although Face Recognition technology has been widely adopted, most existing systems utilize a